THE PAST, PRESENT AND FUTURE OF THE EU LEGAL FRAMEWORK ON FUNDAMENTAL RIGHTS - Uka, Albulena (Horizons - International Scientific Journal, 2021)
This paper examines the legal framework in the field of fundamental rights in the European Union. The main focus will be to depict the position of the fundamental rights in the peculiar legal system of the EU and do so by listing the relevant legal acts and following the evolution of the EU. It will include the Treaties, the Charter of Fundamental Rights in the European Union and secondary legislation. This paper will also analyse the role of the Charter and its prominence on the protection of fundamental rights in the EU. Also, the paper will look at the potential implications that may arise in the future of the EU or in relation with the Member States of the Union.